Does atorvastatin have augmentative effects with sodium valproate in prevention of migraine with aura attacks? A triple-blind controlled clinical trial - Reza Ganji; Nastaran Majdinasab; Saeed Hesam; Nazanin Rostami; Mehdi Sayyah; Adeleh Sahebnasagh (BMC, 2021)
Abstract Background Migraine is a painful and disabling nervous disorder which negatively affects the quality of life. Migraineurs may suffer from a generalized vasomotor dysfunction. Statins improve vasomotor and vascular function, with their pleiotropic effects. We aimed to assess efficacy and safety of adding Atorvastatin to prophylactic regimen in better control of migraine with aura. Methods This triple-blind controlled clinical trial was on 68 patients with migraine with aura. An interval of at least 1 month was given to evaluate vitamin D3 level and eligibility. In patients with vitamin D3 deficiency, the correction with vitamin D supplementation was provided. The patients were randomly assigned to receive atorvastatin 20 mg plus sodium valproate 500 mg or placebo plus sodium valproate 500 mg once a day for 2 months. The patients were evaluated based for the number of attacks and pain severity based on Visual Analogue Scale. Results There was a significant (p = 0.0001) improvement in severity of pain and number of migraine attacks by adding Atorvastin to the prophylactic regimen of patients with migraine with aura. After controlling for variable parameters, the differences between two arms of the study was yet statistically significant (p = 0.0001). A significant number of participants in intervention group were satisfied by their treatment (p = 0.001) with no remarkable side effects (P = 0.315). Conclusions Adding atorvastatin to migraine with aura preventive regimen may help reduce the number of acute attacks and pain severity without causing considerable side effects and led to a better patient satisfaction. Trial registration IRCT20180106038242N1 . Registered: 7 February 2018.